2016
DOI: 10.3109/10641963.2015.1089883
|View full text |Cite
|
Sign up to set email alerts
|

Are increased oxidative stress and asymmetric dimethylarginine levels associated with masked hypertension?

Abstract: Based on these results, it could be said that oxidative stress, and therefore the ADMA level, could have an effect on the etiopathogenesis of MHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…However, it is unknown if they can detect early subtle changes of endothelial function. Only 2 small studies have found elevated plasma ADMA levels in white‐coat and masked hypertensives without comorbidities. To our knowledge, there is no previous study measuring ADMA levels simultaneously in all hypertension phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is unknown if they can detect early subtle changes of endothelial function. Only 2 small studies have found elevated plasma ADMA levels in white‐coat and masked hypertensives without comorbidities. To our knowledge, there is no previous study measuring ADMA levels simultaneously in all hypertension phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports point toward a prominent vascular dysfunction in patients with masked hypertension (MH) and white‐coat hypertension (WCH) compared to normotensive individuals (NT) . Nevertheless, studies on endothelial function markers and their association with macrovascular damage across different hypertension phenotypes are limited …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide deficiency as well as oxidative stress play an important role in arterial hypertension. Likewise, numerous investigations have shown a link between ADMA levels and the occurrence and development of hypertension [60][61][62]. Controversially, there are also studies in the general population which could not prove this association [63].…”
Section: Adma and Sdma In Relation To Vascular Risk Factorsmentioning
confidence: 99%
“…Коэффициенты корреляции для указанных пар показателей составили r=0,416 и r=0,409 соответственно (p<0,05). Полученные в нашем ис-следовании результаты свидетельствуют о том, что при контролируемой АГ на скорость развития ЭД влияют нарушения углеводного и липидного обмена, что в значительной мере согласуется с сообщениями других авторов [14]. Другие параметры липидного профиля во II группе, как и в I группе, не связаны с уровнем ADMA (p>0,05; табл.…”
Section: ðåçóëüòàòûunclassified